Search for long-lived massive charged particles in 1.96 TeV pp collisions. - Aaltonen, T; Adelman, J; Akimoto, T; Alvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; et al. (2009)
We performed a signature-based search for long-lived charged massive particles produced in 1.0 fb-1 of pp[over ] collisions at sqrt[s]=1.96 TeV, collected with the CDF II detector using a high transverse-momentum (pT) muon trigger. The search used time of flight to isolate slowly moving, high-pT particles. One event passed our selection cuts with an expected background of 1.9+/-0.2 events. We set an upper bound on the production cross section and, interpreting this result within the context of a stable scalar top-quark model, set a lower limit on the particle mass of 249 GeV/c2 at 95% C.L.